Zerumbone ameliorates neuropathic pain symptoms via cannabinoid and ppar receptors using in vivo and in silico models - Chia, Jasmine Siew Min; Farouk, Ahmad Akira Omar; Mohamad, Tengku Azam Shah Tengku; Sulaiman, Mohd Roslan; Zakaria, Hanis; Hassan, Nurul Izzaty (MDPI AG, 2021)
Neuropathic pain is a chronic pain condition persisting past the presence of any noxious stimulus or inflammation. Zerumbone, of the Zingiber zerumbet ginger plant, has exhibited anti-allodynic and antihyperalgesic effects in a neuropathic pain animal model, amongst other pharmacological properties. This study was conducted to further elucidate the mechanisms underlying zerumbone’s antineuropathic actions. Research on therapeutic agents involving cannabinoid (CB) and peroxisome proliferator-activated receptors (PPARs) is rising. These receptor systems have shown importance in causing a synergistic effect in suppressing nociceptive processing. Behavioural responses were assessed using the von Frey filament test (mechanical allodynia) and Hargreaves plantar test (thermal hyperalgesia), in chronic constriction injury (CCI) neuropathic pain mice. Antagonists SR141716 (CB1 receptor), SR144528 (CB2 receptor), GW6471 (PPARα receptor) and GW9662 (PPARγ receptor) were pre-administered before the zerumbone treatment. Our findings indicated the involvement of CB1, PPARα and PPARγ in zerumbone’s action against mechanical allodynia, whereas only CB1 and PPARα were involved against thermal hyperalgesia. Molecular docking studies also suggest that zerumbone has a comparable and favourable binding affinity against the respective agonist on the CB and PPAR receptors studied. This finding will contribute to advance our knowledge on zerumbone and its significance in treating neuropathic pain.